2002
DOI: 10.1530/eje.0.1470701
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced serum oestrogen levels and highly steroidogenic, luteinized atretic follicles in the ovaries of the Djungarian hamster (Phodopus sungorus) kept under a short photoperiod from birth

Abstract: Enhanced serum oestrogen levels and highly steroidogenic, luteinized atretic follicles in the ovaries of the Djungarian hamster (Phodopus sungorus ) kept under a short photoperiod from birth R van den Hurk, G Dijkstra and F H de Jong AbstractObjective: In contrast to the elaborate information available on the effects of the photoperiod on the testes of hamsters, little is known about the influence on their ovaries. This study aimed to describe the ovarian follicular development and steroid hormone production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…When we determined the photoperiod-induced differences in uterine size were evident by 3 wk of age, we then focused our investigation on LD and SD hamsters at 4 wk of age for the following reasons: 1. The highest E2 concentration reported by van den Hurk et al (2002) was in SD females at this age and the LD-SD difference in serum E2 concentration at 4 wk was substantial (approximately 5-fold), and 2. Neither LD nor SD females have matured by this age, as indicated by the lack of vaginal patency (Place et al 2004) and the absence of any signs that ovulations had occurred (van den Hurk et al 2002).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…When we determined the photoperiod-induced differences in uterine size were evident by 3 wk of age, we then focused our investigation on LD and SD hamsters at 4 wk of age for the following reasons: 1. The highest E2 concentration reported by van den Hurk et al (2002) was in SD females at this age and the LD-SD difference in serum E2 concentration at 4 wk was substantial (approximately 5-fold), and 2. Neither LD nor SD females have matured by this age, as indicated by the lack of vaginal patency (Place et al 2004) and the absence of any signs that ovulations had occurred (van den Hurk et al 2002).…”
Section: Introductionmentioning
confidence: 78%
“…The highest absolute concentration (~2400 pmol/L or ~ 654 pg/mL) was measured in SD females at 4 wk of age. Given the growth promoting effects of E2 on the uterus (Scotti et al 2007), we found the report of higher E2 in SD hamsters (van den Hurk et al 2002) to be perplexing. Unfortunately, van den Hurk et al (2002) did not report uterine mass data, thus the present study is the first to investigate the apparent mismatch between serum E2 concentrations and uterine growth in P. sungorus .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Specifically, these photoperiodic cues establish and modify the hamster's developmental trajectory via changes in somatic and/or reproductive development. For example, it is well known that photoperiodic information can be transmitted in utero via maternal melatonin secretion, and this prenatal signal can affect postnatal photoperiodic responses (Horton 1985, Stetson et al 1986, Lee et al 1987, Weaver et al 1987, Elliott & Goldman 1989) and the reproductive development of young (Prendergast et al 2000, Kauffman & Zucker 2002, Tuthill et al 2005. More recent studies have shown that perinatal photoperiod can have lasting effects on circadian rhythms expressed by clock neurons, wheel-running behavior (Ciarleglio et al 2011), depressive-and anxiety-like behaviors , and immune responses (Weil et al 2006).…”
Section: Gonadotropin Suppression In Ldsmentioning
confidence: 99%
“…Exposure to 12–14 weeks in short (8h light: 16 h dark per day; SD) photoperiod is sufficient to induce regression of the ovaries, anovulation, and decreased estradiol production (Moffatt-Blue, et al 2006; Salverson et al 2008; Schlatt et al 1993). Reproductively regressed hamsters are characterized by the absence of corpora lutea (CL) in the ovaries, decreases in uterine mass and plasma concentration of estradiol, and the presence of eosiniphilic terminal atretic follicles, structures typically found only in regressed ovaries (van den Hurk et al 2002; Moffatt-Blue, et al 2006; Kabithe & Place 2008). Once transferred to long day photoperiods of 16 hours of light and 8 hours of darkness per 24-hour period (long days; LD), female hamsters will rapidly regain reproductive function (Salverson et al 2008; Shahed & Young 2008).…”
Section: Introductionmentioning
confidence: 99%